Pengaruh Profitabilitas, Ukuran Perusahaan, Tingkat Utang dan Kualitas Audit Terhadap Agresivitas Pajak - Shinta; Agus Sihono (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2023)
This study aims to examine the effect of profitability, firm size, debt levels and audit quality on tax aggressiveness. This study used a purposive sampling method to collect secondary data samples from the annual reports of 18 food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) with a research period of 2020-2022. The analytical method used is multiple linear regression using the SPSS version 25 program. Tax aggressiveness is measured using the Effective Tax Rate (ETR), profitability is measured using Return On Assets (ROA), company size is measured by firm size, debt levels are measured using Debt Assets Ratio (DAR) and audit quality are measured using a dummy variable. The results of this study indicate that profitability and debt levels have a positive effect on tax aggressiveness, while firm size and audit quality have no effect on tax aggressiveness. The implications of this study ensure that the profits obtained by the company are not the result of tax aggressiveness.